سوء اندمال كسور النهاية القاصية للكعبرة (النتائج الوظيفية) - حلوم, غياث (Latakia University Journal -Medical Sciences Series, 2017)
إن كسور النهاية القاصية للكعبرة داخل المفصل لها نتائج سيئة أكثر بكثير من كسور النهاية القاصية للكعبرة خارج المفصل من حيث مجال حركتي الثني والبسط, الانحراف الكعبري والانحراف الزندي للمفصل .إن قصر الكعبرة واتجاه السطح المفصلي للكعبرة لابد من إعادة تصحيحهما . سلامة السطح المفصلي للكعبرة يلعب دور مهم في تقرير النتائج. إن تبدل السطح المفصلي للكعبرة أكثر من 1 مم تحدث الم معند على العلاج وقسط مفصلي فيما بعد. أكثر من 92 % من المرضى الذين كان عندهم عدم تطابق في السطح المفصلي للكعبرة مع افتراق أكثر من 2 مم حدث لديهم تنكس في المفصل الكعبري الرسغي. من خلال فحص المرضى الذين حدث لديهم اندمال مع قصر في الكعبرة أكثر من 2 مم, لاحطنا نقص في مجال حركة مفصل المعصم ( الثني /البسط , الكب / الاستلقاء) بشكل أكثر من المرضى الذين لم يحدث عندهم قصر في الكعبرة. أيضا لم نتمكن من إيجاد إحصائية كافية عن الألم أثناء الحركة.The intraarticular fracture of distal end of radius have bad returns more than extra articular fractures whereform the range of motion in flexion and extension, radial variance and ulnar variance of the joint. Shortness of the radius and the direction of articular surface of the radius should be corrected. The integrity of radial articular surface play an important rule in determining results. Displacement of the articular surface more than 1 mm cause an obstinate pain and synarthrophysis thereafter. More than 92% of the patients with disalignment of articular surfaces with space more than 2 mm end with arthrosis in the radial carpal joint. Through examening patients with union with shortness of radius more than 2 mm, we notices recuction of the wrist range of motion) flextion-extention- pronation -supination) more than patients without shortness. Also we couldnt find sufficient statitics about the pain during motion.